2019
DOI: 10.1002/dvdy.43
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of differential gene expression during chick periocular neural crest differentiation into corneal cells

Abstract: Background: Multipotent neural crest cells (NCC) contribute to the corneal endothelium and keratocytes during ocular development, but the molecular mechanisms that underlie this process remain poorly understood. We performed RNA-Seq analysis on periocular neural crest (pNC), corneal endothelium, and keratocytes and validated expression of candidate genes by in situ hybridization. Results: RNA-Seq profiling revealed enrichment of genes between pNC and neural crest-derived corneal cells, which correspond to pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 145 publications
(212 reference statements)
3
14
0
Order By: Relevance
“…Zfp469 remains expressed at E16.5, by which point the presumptive stroma is wellestablished. This expression pattern agrees with that reported for ZNF469 during development of the cornea in the chick (Bi and Lwigale, 2019) and coincides with the induction of temporally regulated signalling pathways important to corneal development, and with increasingly high expression levels of Col1a1, Col1a2 and other ECM components important in the stroma (Bard and Kratochwil, 1987;Ma and Lwigale, 2019). As the cornea matures, up to 8 weeks of age in the mouse, or 3 years of age in humans, collagen fibrils are further organised into additional layers of the established lamella.…”
Section: Discussionsupporting
confidence: 91%
“…Zfp469 remains expressed at E16.5, by which point the presumptive stroma is wellestablished. This expression pattern agrees with that reported for ZNF469 during development of the cornea in the chick (Bi and Lwigale, 2019) and coincides with the induction of temporally regulated signalling pathways important to corneal development, and with increasingly high expression levels of Col1a1, Col1a2 and other ECM components important in the stroma (Bard and Kratochwil, 1987;Ma and Lwigale, 2019). As the cornea matures, up to 8 weeks of age in the mouse, or 3 years of age in humans, collagen fibrils are further organised into additional layers of the established lamella.…”
Section: Discussionsupporting
confidence: 91%
“…To define the expression of Npnt mRNA and protein distribution during this process, we performed section in situ hybridization and immunohistology, respectively. Consistent with our RNA-seq data (Bi & Lwigale, 2019), we found that Npnt is undetectable in the pNC by embryonic day (E) 4 and in the presumptive corneal endothelium at E5, but it is primarily expressed in the retinal pigment epithelium (RPE) and presumptive lens fiber cells at these time points (Fig. 1A, B).…”
Section: Npnt Mrna and Protein Are Expressed During Early Ocular Developmentsupporting
confidence: 89%
“…Very little is known about the function of the corneal ECM during early development. Here, we focus on Npnt, which we recently found in our RNA-seq study (Bi & Lwigale, 2019) to be upregulated during early development of the chick cornea. Specifically, we have identified novel expression of Npnt and its Itga8 receptor at critical timepoints of corneal development.…”
Section: Discussionmentioning
confidence: 99%
“…Type II and type IX collagens are replaced by type I and type V as principal components of the secondary stroma. Multipotent periocular cells, originating in the neural crest, undergo distinctive alterations in gene expression as they migrate to form corneal endothelium and keratocytes (Bi and Lwigale, 2019). The latter synthesise the mature stroma, and there is strong evidence that cellular mechanisms exert a profound influence upon the organisation and orientation of matrix they deposit (Birk and Trelstad, 1984; Young et al, 2014; Koudouna et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%